Reposition and Role of Non-Governmental Organizations in North Sumatera Post-New Order: A Study of KSPPM, BITRA Indonesia, And PESADA - Dimpos Manalu; Johnson Pasaribu; Artha Lumbantobing; Vera A Pasaribu; Susi Yanti Halawa (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to uncover the role and repositioning of non-governmental organizations (NGOs) in North Sumatra in the post-New Order era. Specifically, this study aims to uncover how NGOs reposition themselves towards the state/government, the market, and civil society—three major entities widely recognized in Public Administration studies. This is crucial considering that NGOs—as one of the important democratic actors in community empowerment and democratization in Indonesia—are situated within a constantly changing national socio-political landscape, as well as a global context that increasingly emphasizes the importance of multi-stakeholder collaboration. This study—taking into account the issues and areas discussed—focuses on three institutions: KSPPM, BITRA Indonesia, and PESADA. Using a qualitative-descriptive method, this study concludes several things: first, during the Reformation era, NGOs have repositioned themselves, no longer as opposition to the government, but as